The Effect of Motivation and Work Discipline on Employee Performance PT Bagus Jaya Textile - Anggri Arianto; Muji Rahayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study is to determine the impact of motivation and work discipline on employee performance. The population is the employees of PT Bagus Jaya Textil. This research uses quantitative, descriptive, and verification methods. Data collection was carried out by distributing Likert scale-based questionnaires 1-5 through Google Forms to 76 employees selected using a purposive sampling technique. The number of samples was determined by the formula. Data processing was carried out using SPSS version 29, including multiple linear regression tests, F tests, t tests, and correlation and determination coefficient analysis. The results showed that motivation and work discipline together have a significant effect on employee performance at PT Bagus Jaya Textile. Partially, motivation and work discipline have a positive and significant effect on employee performance at PT Bagus Jaya Textile. The results show that work discipline has a more dominant influence. These findings emphasize the importance of integrating motivation and work discipline improvement programs in human resource strategies to support optimal performance in the textile industry environment.